Financial Technology and Digital Marketing on MSMEs and their Impact on Financial Performance and Business Sustainability - Noviana Yaniar; Agus Dwi Sasono; Agus Sukoco; Amrun Rosyid (LPPM of NAROTAMA UNIVERSITY, 2021)
Purpose: This study aims to analyze the effect of financial technology and digital marketing on MSMEs and their impact on financial performance and business sustainability. Design/methodology/approach: The research uses an explanatory quantitative approach. The population in this study were all members of the Metropolia community, amounting to 155 people. The sampling technique used was purposive Data collection is done using google Forms. The data collected were analyzed using SEM-PLS. Findings: Fintech has a positive and significant influence on the financial performance of MSMEs. Digimart has a significant influence on the financial performance of MSMEs. Fintech has a significant influence on the business sustainability of MSMEs. Digimart does not have a significant influence on the business sustainability of MSMEs. Financial performance has a significant positive influence on the business sustainability of MSMEs. Paper type: Research paper